Zingiber zerumbet L. essential oil‐based chitosan nanoemulsion as an efficient green preservative against fungi and aflatoxin B1 contamination. Issue 1 (13th December 2020) - Deepika,; Singh, Akanksha; Chaudhari, Anand Kumar; Das, Somenath; Dubey, Nawal Kishore
Abstract : Abstract: The present study envisages the potential application of chitosan‐coated Zingiber zerumbet essential oil nanoemulsion (ZEO‐CsNE) as green antimicrobial preservative against Aspergillus flavus, aflatoxin B1 (AFB1 ), and lipid peroxidation of stored functional foods. GC‐MS analysis of ZEO exhibited the abundance of cis‐geraniol (15.53%) as the major component. ZEO‐CsNE showed biphasic release profile during in vitro release study conducted for 10 days. The ZEO‐CsNE inhibited the growth of A. flavus (strain AF‐LHP‐SH1) and AFB1 production at 1.0 and 0.8 µL/mL, respectively. Interestingly, considerable reduction in ergosterol biosynthesis followed by enhanced leakage of vital cellular contents and methylglyoxal inhibition represents novel antifungal and antiaflatoxigenic mechanism of action, respectively. Further, ZEO‐CsNE inhibited lipid peroxidation and AFB1 production in postharvest Salvia hispanica seeds during in situ trial and presented favorable safety profile (median lethal dose [LD50 ] = 29, 114 µL/kg) for male mice. Based on overall observations, ZEO‐CsNE could be recommended as a green antimicrobial substitute of synthetic preservatives for in vitro and in situ protection of functional food samples. Practical Application: Food industries are facing enormous amount of burden coming from fungal and aflatoxin contamination that can cause severe adverse effects to humans. Essential oils (EOs) are well known for their food preservative efficacy; however, some limitations such as oxidative instability in open system may limit their application directly into food system. The encapsulation of the EOs into polymeric matrix could provide a barrier that will protect the EOs from degradation. This research could provide a basis for utilization of EO after encapsulation into chitosan nanoemulsion for industrial‐scale application for preservation of stored functional foods from fungal and aflatoxin contamination.